(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the changes in quality of life (QoL) in non-small cell lung cancer (NSCLC) patients with brain metastases after treatment with a combination of Gamma Knife radiosurgery and TKIs. Subjects and methods: A longitudinal, prospective descriptive study was conducted on 43 NSCLC patients with brain metastases who received Gamma Knife radiosurgery combined with TKIs from January 2023 to December 2024. Results: At the 6-month follow-up, most aspects of QoL remained stable. Several functions and symptoms showed significant improvement, such as: emotional function, fatigue, insomnia, future uncertainty, and motor dysfunction (improvement > 10 points, p<0,05). Meanwhile, rash and hair loss increased significantly. Patients with a low Karnofsky score and neurological symptoms before treatment showed better improvement in cognitive and motor functions (p<0,05). Meanwhile, patients treated with first and second generation TKIs developed skin rash more frequently than those treated with third generation TKIs (p=0.03). Conclusion: The QoL of NSCLC patients with brain metastases after treatment with combined Gamma Knife radiosurgery and TKIs was maintained stably, with several functions and symptoms showing significant improvement.